A Comparative Study of English and Non-English Major University Students' Motivation to Learn English Oral Communication - Quadir, Mst. Moriam (EAST WEST JOURNAL OF HUMANITIES, 2011)
This study examines the differences in motivations of English and non-English major university students in Bangladesh to learn English oral communication. Altogether 355 (184 English and 171 non-English majors) university students participated in this study. To measure learners' motivation a modified versions of the questionnaire constructed by Schmidt's et al (1996) was administered. In order to figure out the significant differences between the two groups an independent sample t-test was performed on each questionnaire item and on motivational subscales. Pearson correlations (2-Tailed) were analyzed on motivation data of both groups to understand the interactions among motivational subscales. Some similarities and differences between the groups are found from the analyses. Based on the findings of this study some suggestions are proposed for their pedagogical usefulness.